Modeling home property listings’ time-on-market duration and listing outcome using copula-based competing risk method - Liu, Yicong; Shakib, Saeed; Miller, Eric J.; Habib, Khandker Nurul (Journal of Transport and Land Use, 2024)
Modeling housing market dynamics is an important component of land use and transport interaction (LUTI) models, particularly for microsimulation models and how they handle the market clearance mechanism. However, most of these models include key assumptions not derived or validated through empirical testing, such as when and what action a seller would take if a property could not be sold within an expected time. However, these are key decision elements of the housing market clearance process. To fill this research gap, this study uses real estate sale listing data to investigate the factors influencing a property listing’s time-on-market (TOM) duration, listing outcome, and correlation. A copula-based structure is developed to jointly estimate the TOM and listing outcome through a competing hazard duration model and a nested logit model. The results show statistically significant and positive correlations between the TOM of terminated listings and termination choices (i.e., whether the terminated listing will be withdrawn from the market, converted to a lease, or re-listed as a sale). This implies that the unobserved factors that may increase a seller’s probability of terminating a listing would decrease its TOM duration until the termination. It is also found that an increase in the asking price of a property listing can significantly increase its TOM duration and probability of being terminated. The copula-based joint model can be integrated into a LUTI microsimulation framework to parameterize the maximum TOM duration of each simulated property for sale in the housing market, improving its market-clearing process to represent real-world behavior better.